2018
DOI: 10.4236/jss.2018.69016
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Model of Cross-Border Medical Tourism Decision-Making under the Background of Globalization

Abstract: With the help of the wave of globalization, the new industry market is constantly emerging, showing a clear trend of "reverse globalization". Among them, cross-border medical tourism and related industries are particularly effective. The flow of cross-border medical tourism patients has changed dramatically. What is the development of international medical tourism industry? Which factors make the "reverse globalization" phenomenon occur on cross-border medical tourism? How do patients decide their medical tour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…The whole life cycle information of cross-border products, especially the cross-border degree information, can be completely and accurately recorded and stored in the product information traceability system supported by blockchain, and consumers can fully trust the cross-border degree of products [ 23 ]. Both manufacturers and retailers of cross-border products use the blockchain platform to conduct transactions, and when the number of transactions reaches a certain level, both parties will gain value from the good transaction records.…”
Section: Cross-border Supply Chain Decisions In a Blockchain Scenariomentioning
confidence: 99%
“…The whole life cycle information of cross-border products, especially the cross-border degree information, can be completely and accurately recorded and stored in the product information traceability system supported by blockchain, and consumers can fully trust the cross-border degree of products [ 23 ]. Both manufacturers and retailers of cross-border products use the blockchain platform to conduct transactions, and when the number of transactions reaches a certain level, both parties will gain value from the good transaction records.…”
Section: Cross-border Supply Chain Decisions In a Blockchain Scenariomentioning
confidence: 99%
“…There are also unrestricted monthly visits by these physicians under the umbrella of so-called clinics for consultation and further treatment in India. Sun (2018) suggested that health treatment cost, excellence of care, hospital accreditation, and doctor experience inspire patients' medical facility choice. Ajmera et al (2015) explained that the international sections of Indian hospitals ensure quality services for international patients.…”
Section: Relationship Between Outbound Medical Travel and Different Factorsmentioning
confidence: 99%